Cement - Goldstein, Nechama (Israel, 2006)
Portrait of a family living in a village in East Jerusalem, surrounded by the separation wall and trying to cope with the Israeli-Palestinian conflict. “Cement” is the story of a mother of 12 children who is unable to provide for them. It is a story of a family torn apart. “Cement” presents a reality in which children are forced to grow up too fast, some are forced to drop out of school and provide for the family while others are thrown into jail.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films